Photolithography: Two‐Photon Nanolithography Enhances the Performance of an Ionic Liquid–Polymer Composite Sensor (Adv. Funct. Mater. 11/2015). (March 2015) - Bakhtina, Natalia A.; Loeffelmann, Ute; MacKinnon, Neil; Korvink, Jan G.
Abstract : A novel ionic liquid–polymer composite material is reported by J. G. Korvink and co‐workers on page 1683, alongside an approach for its patterning by two‐photon nanolithography. The unique properties of the material are combined with a single‐step process for its 3D structuring, having nanometer resolution and high aspect ratio. A proof‐of‐concept multifunctional sensor for temperature and relative humidity sensing is demonstrated.